Pricing, risk, and performance measurement in practice : the building block approach to modeling instruments and portfolios - Schwerdt, Wolfgang (Elsevier and Mondo Visione world capital markets series., 2010)
How can managers increase their ability to calculate price and risk data for financial instruments while decreasing their dependence on a myriad of specific instrument variants? Wolfgang Schwerdt and Marcelle von Wendland created a simple and consistent way to handle and process large amounts of complex financial data. By means of a practical framework, their approach analyzes market and credit risk exposure of financial instruments and portfolios and calculates risk adjusted performance measures. Its emphasis on standardization yields significant improvements in speed and accuracy. Schwerdt and von Wendland's focus on practical implementation directly addresses limitations imposed by the complex and costly processing time required for advanced risk management models and pricing hundreds of thousands of securities each day. Their many examples and programming codes demonstrate how to use standards to build financial instruments, how to price them, and how to measure the risk and performance of the portfolios that include them. Feature: The authors have designed and implemented a standard for the description of financial instruments Benefit: The reader can rely on accurate and valid information about describing financial instruments Feature: The authors have developed an approach for pricing and analyzing any financial instrument using a limited set of atomic instruments Benefit: The reader can use these instruments to define and set up even very large numbers of financial instruments. Feature: The book builds a practical framework for analysing the market and credit risk exposure of financial instruments and portfolios Benefit: Readers can use this framework today in their work and identify and measure market and credit risk using a reliable method.